An investigation of marketing via mobile devices : attitudes of Croatian marketing experts - Dobrinić, Damir, ekonomist (Array, 2008)
Summary: Marketing activities supported by mobile devices offer great opportunities for direct communication with consumers without the barriers of time, place, location and other. This article explores opinions and expectations Croatian marketing experts have towards use of m-advertising and other available advertising media, where we take the perspective of marketing experts to predict the future of m-marketing and m-advertising in Croatia. The paper also discusses the relevance of m-advertising and investigates the future of m-marketing and m-advertising in Croatia. This research focuses mainly on understanding the potential and effectiveness of the use of mobile phones as a promotional medium, but we also try to recognize the level of concern of marketing experts associated with spam, relating to privacy intrusion and ethics components in m-advertising. Privacy and ethics concerns could create resistance to the adoption of m-advertising. Media selection becomes the most critical factor for the success of a promotional and advertising marketing campaign. Croatian experts still consider TV or newspapers the best way to reach a large number of potential consumers, but what are their expectations towards mobile advertising? To answer this question, we built a model that links attitudes towards advertising via classical media to the intention to use m-advertising